Qualitative evaluation of a physical activity health promotion programme for people with intellectual disabilities in a group home setting. (23rd August 2017) - Dixon‐Ibarra, A; Driver, S; Nery‐Hurwit, M; VanVolkenburg, H
Abstract : Background: There is a lack of health promotion programming designed to change the physical activity environment of the group home setting. The Menu‐Choice programme assists staff in creating physical activity goals alongside residents with intellectual disabilities and provides strategies to incorporate activity into the group home schedule. The purpose of this study was to complete a process evaluation of Menu‐Choice utilizing qualitative methods. Methods: Twelve participants, who completed a 10‐week pilot intervention ( n = 7 staff, mean age 42; n = 5 residents, mean age 52), participated in face‐to‐face interviews. Participants represented five group home sites involved in the intervention. Results: Meta‐themes included: (i) Programme training, (ii) Programme implementation, (iii) Programme physical activity, (iv) Programme barriers, (v) Programme facilitators and (vi) Programme feedback. Conclusions: Changes in programme training and simplified programme materials are needed to accommodate identified barriers for implementation. The importance of obtaining increased agency support and policy change is highlighted.